Literasi Media Siswa dalam Penggunaan Internet di Sekolah Alam Bogor - Wahyuni Choiriyati; Vivit Wardah Rufaidah; Ade Tuti Turistiati (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
This media literacy research describes the reality of using internet media by students of Alam Middle School-Bogor (SMP Alam Bogor). The school has the concept of integration consisting three pillars of education and a key factor in humanity's excellence as an element of teaching. The three pillars include faith, knowledge and leadership with the motto more than a school, it's a community. SMP Alam Bogor was chosen because it minimizes the use of paper in the education process. In addition, all communication and learning activities are carried out through a login system on the school website. The purpose of this study is to analyze phenomena in more detail and narrative with the Individual Competence Framework as the main basis for measuring and describing media literacy for students of SMP Alam Bogor. The population in this study were all students of SMP Alam Bogor, with 68% male students and 32% female students. The questionnaire was chosen as a data collection technique. The sample was determined by simple random sampling with the aim that all populations have the same opportunity to become respondents. The results showed 48% of students at SMP Alam Bogor used chatting facilities to discuss school work issues and 31% discussed personal problems. The ability of students to use the internet to improve media literacy is quite good, it is seen that 87.8% of students are able to produce media content in the form of blogs that they make themselves, while the remaining 12.2% do not have blogs. The analysis showed that the majority of students at SMP Alam Bogor solved the problem independently (36.6%) and asked friends, relatives, teachers when they had difficulty in accessing the internet (21.9%). The category of social competence in the use of the internet places students of SMP Alam Bogor in the medium category. AbstrakRiset literasi media ini mendeskripsikan realitas penggunaan media internet oleh siswa SMP Alam Bogor yang merupakan sekolah berkonsep integrasi tiga pilar pendidikan. Sekolah Alam menempatkan faktor kunci keunggulan umat manusia sebagai elemen pengajaran. Tiga pilar tersebut meliputi iman, ilmu dan kepemimpinan dengan motto more than a school, it’s a community. SMP Alam Bogor dipilih karena meminimalkan pemakaian kertas dalam proses pendidikan. Selain itu, aktivitas komunikasi dan pembelajaran semua dilakukan melalui system login di website sekolah. Tujuan penelitian ini untuk menganalisis fenomena secara lebih rinci dan naratif dengan Individual Competence Framework sebagai dasar utama mengukur dan menggambarkan media literacy siswa SMP Alam (SM) Bogor. Populasi dalam penelitian adalah seluruh siswa SMP Alam Bogor sebanyak 68 % siswa laki-laki dan 32% siswa perempuan. Kuisioner dipilih sebagai teknik pengumpulan data. Sampel ditentukan secara simple random sampling dengan tujuan semua populasi memiliki kesempatan sama menjadi responden. Hasil penelitian menunjukkan 48 % siswa SMP Alam Bogor memanfaatkan fasilitas chatting untuk mendiskusikan masalah tugas sekolah dan 31 % diskusi masalah pribadi. Kemampuan siswa dalam memanfaatkan internet untuk meningkatkan media literacy cukup baik, terlihat 87,8% siswa mampu memproduksi konten media berupa blog yang mereka buat sendiri, sedangkan sisanya 12,2% tidak memiliki blog. Hasil analisis menunjukkan bahwa sebagian besar siswa SMP Alam Bogor menyelesaikan permasalahan secara mandiri (36,6%) dan bertanya kepada teman, saudara, guru ketika mereka mengalami kesulitan dalam mengakses internet (21,9%). Adapun kategori kompetensi social dalam penggunaan internet menempatkan siswa SMP Alam dalam kategori medium.